The global perspective on the evolution of nurse-related research in primary malignant bone tumors from 2004 to 2025 - Nianzhe Sun; Laiyu Xu; Jinfei Fu; Panfeng Wu; Liming Qing; Lingli Peng; Juyu Tang (Medicine, 2026)
Background: Primary malignant bone tumors, as diseases that mostly occur in adolescence, seriously affect all aspects of the lives of patients and their families. Effective bone tumor nursing is essential to maintain or improve patients’ quality of life. Consequently, investigating bone tumor nursing is of utmost importance. This study aimed to provide a comprehensive, up-to-date synthesis of all published bone tumor nursing research articles and predict future areas of research and emerging trends. Methods: A bibliometric analysis was conducted using the Web of Science Core Collection to identify and analyze nursing research publications on primary malignant bone tumors from January 1, 2004, to September 12, 2025. The analysis and visualization were performed using various scientometric tools. Key characteristics of the publications, including country of origin, institutions, authors, journals, keywords, and references, were thoroughly examined. Results: A total of 686 studies were included in the analysis, with 5376 authors, 70 countries, and 1422 institutions publishing research focused on nurse-related studies in primary malignant bone tumors. The United States and Memorial Sloan Kettering Cancer Center led the lists of publications. The most prolific cited and co-cited authors were Oeffinger, Kevin C, and Bacci, G, respectively. Pediatric Blood & Cancer published the most articles, whereas Journal of Clinical Oncology was the most frequently cited journal. The analysis of keyword co-occurrence and literature co-citation identified several emerging hotspots and trends in the field of primary malignant bone tumor nursing, including prognostic evaluation, clinical intervention, and subtype-targeted nursing care. Conclusion: In recent years, the advancement in nurse-related research in primary malignant bone tumors has accelerated rapidly. A comprehensive bibliometric analysis was utilized to verify the prominent areas of investigation and anticipate future research directions, with the aim of providing valuable insights and recommendations for future studies.